Effect of uniaxial stretching on the structural and dielectric properties of melt cast Nylon 11 films. Issue 2 (10th December 2022) - Jain, Mayank; Mutlu, Zeynep; Mao, Jiahao; Zhou, Jierui; Zhou, Peinan; Wu, Chao; Cao, Yang; Cakmak, Mukerrem
Abstract: In this study, the effect of processing on the structural and dielectric properties of Nylon 11 melt cast film was studied. Capacitor grade thin films were cast using a film extruder and stretched uniaxially and real‐time mechano‐optical data were acquired at temperatures ranging from solid state all the way to partially molten state. These studies were supplemented with offline WAXS, SAXS, and DSC to develop a complete understanding of processing induced structural changes and their relation to dielectric properties. When stretched in the solid‐state, preferential crystalline and amorphous chain orientation levels increased as a function of strain while the long spacing remained constant due to lamellar slippage. Processing in the partially molten state led to the formation of new lamellae with larger long spacings. It was also observed that the dielectric properties of Nylon 11 were strongly dependent on the crystallinity and crystal phase, with higher crystallinity of the α′ phase giving higher electrical breakdown strength. When films were stretched to 3X solid and partially molten states, together with crystallinity, the breakdown strength is increased, while the dielectric constant and loss decrease. Since crystalline regions are stiffer, they form effective barriers to hot carriers, retarding the electric breakdown. Abstract : Uniaxial stretching experiments of melt cast Nylon 11 films was performed and real‐time mechano‐optical data was acquired. It was found the uniaxial stretching effects dielectric properties, with changes in dielectric loss, constant and breakdown strength being influenced by crystallinity and crystalline phase after stretching, as well as stretching temperature used. Breakdown strength increased when films were stretched in the solid state.